A Computer-Accessed Microfiche Library - Zimmerman, R. G. J. (Information Technology and Libraries, 1974)
This paper describes a user-interactive system for the selection and display of pictorial information stored on microfiche cards in a computer-controlled viewer. The system is designed to provide rapid access to photographic and graphical data. It is intended to provide a library of photographs of planetary bodies and is currently being used to store selected Martian and lunar photography.